Development of the BG-Malaria trap as an alternative to human-landing catches for the capture of Anopheles darlingi - GAMA, Renata Antonaci (2015)
Although the human-landing catch (HLC) method is the most effective for collecting anthropophilic anophelines, it has been increasingly abandoned, primarily for ethical considerations. The objective of the present study was to develop a new trap for the collection of Anopheles darlingi . The initial trials were conducted using the BG-Sentinel trap as a standard for further trap development based on colour, airflow direction and illumination. The performance of the trap was then compared with those of the CDC, Fay-Prince, counterflow geometry trap (CFG) and HLC. All trials were conducted outdoors between 06:00 pm-08:00 pm. Female specimens of An. darlingi were dissected to determine their parity. A total of 8,334 anophelines were captured, of which 4,945 were identified as An. darlingi . The best trap configuration was an all-white version, with an upward airflow and no required light source. This configuration was subsequently named BG-Malaria (BGM). The BGM captured significantly more anophelines than any of the other traps tested and was similar to HLC with respect to the number and parity of anophelines. The BGM trap can be used as an alternative to HLC for collecting anophelines.